Answer:
Step 1: [tex]z*1+z*1+z*1+z*1=[/tex]
Step 2: [tex]z(1+1+1+1)=[/tex]
Step 3: [tex]z*4=[/tex]
Step 4: [tex]z*4 = 4z[/tex]
Step-by-step explanation:
Given
[tex]z+z+z+z = 4z[/tex]
Required
Match the steps with equivalent properties
Step 1: Multiplicative Identity Property
This states that:
[tex]x = 1 * x[/tex]
So, the expression becomes:
[tex]z*1+z*1+z*1+z*1=[/tex]
Step 2: Distributive Property
This states that:
[tex]ab + bc = b(a+c)[/tex]
So, the expression becomes
[tex]z*1+z*1+z*1+z*1=[/tex]
[tex]z(1+1+1+1)=[/tex]
Step 3: Addition
Here, we simply add the expressions in the bracket
[tex]z(1+1+1+1)=[/tex]
[tex]z(4) =[/tex]
[tex]z*4=[/tex]
Step 4: Commutative Property of Multiplication
This states that:
[tex]ab=ba[/tex]
So, we have:
[tex]z*4=[/tex]
[tex]z*4 = 4*z[/tex]
[tex]z*4 = 4z[/tex]